Achieved systolic blood pressure and cardiovascular outcomes in advanced chronic kidney disease - Ehab Al-Sodany; Karolina Szummer; Joakim Österman; Caroline E Dietrich; Juan-Jesus Carrero; Olof Heimburger; Peter Barany; Marie Evans (Clinical Kidney Journal, 2026)
Abstract Background In advanced chronic kidney disease (CKD) evidence for lower systolic blood pressure (SBP) targets is limited and guideline recommendations are conflicting. We investigated the association between achieved SBP and major adverse cardiovascular events (MACE) in nephrology-referred patients with CKD. Methods In this nationwide, observational cohort from the Swedish Renal Register–chronic kidney disease (SRR-CKD), we included adults with CKD stages 3–5 referred to nephrology outpatient clinics between 2006 and 2017. Mean office SBP during the first year was categorized in incrementally higher SBP groups with 130–<140 mmHg as reference. The primary outcome was MACE; secondary outcomes were its components and all-cause death, analyzed using cause-specific multivariable-adjusted flexible parametric survival models. Results Among 23 317 patients (median age 72 years; 64% men; median eGFR 24 ml/min/1.73 m²), over a median follow-up of 2.5 years, 8 556 (37%) experienced MACE and 7 686 (33%) died. Compared with SBP 130–<140 mmHg, SBP 120–<130 mmHg was associated with lower risks of MACE (adjusted hazard ratio [HR] 0.93, 95% confidence interval [CI] 0.87–0.99) and all-cause mortality (HR 0.93, 95% CI 0.87–0.99), whereas SBP ≥160 mmHg was associated with higher risks of MACE (HR 1.38, 95% CI 1.28–1.49) and death (HR 1.29, 95% CI 1.20–1.38). MACE risk was non-proportional and declined over time in patients with SBP 100–<120 mmHg, demonstrating lower MACE risk compared to 130-<140 after 3 years. In continuous analyses, MACE risk was lowest around 125 mmHg and increased at higher SBP levels. Conclusions In nephrology-referred patients with advanced CKD, achieved SBP around 120–<130 mmHg (near 125 mmHg) was associated with the lowest cardiovascular and mortality risk, while SBP ≥140 mmHg, especially ≥160 mmHg, was consistently associated with higher MACE risk.